Jessica's dilemma: competing loyalties. Issue 4 (3rd July 2017) - Rua, Tuvana; Lawter, Leanna; Andreassi, Jeanine; York, Christopher
Abstract : Synopsis: "Jessica's dilemma: honesty or loyalty" is the true story of a Staff Accountant, Jessica, who discovered embezzlement by the controller, Michael. Jessica worked at a US subsidiary of a multinational organization. One of the company's vendors contacted Jessica regarding unpaid invoices. Following up on the inquiry, Jessica found suspicious manual journal entries in the general ledger. When she questioned her boss, Michael, about her findings, he first denied the situation, then blamed another employee, and ultimately tried to intimidate Jessica so that she would not press the issue. Jessica's investigation led to the discovery that Michael had been embezzling money from the company. To complicate matters, Jessica and her husband had a close relationship with Michael and his wife outside the office. Jessica had to make a choice between being loyal to a family friend and being honest and loyal toward her employer. Research methodology: The authors obtained the information for this case from the staff accountant and her husband via a series of interviews. The information was verified via publicly available news articles on the presented case. Additionally, legal documents, which were publicly available, were also used for information. The name of the company and the names of the individuals in the case were changed to protect the identities and privacy of the involved parties. Relevant courses and levels: An instructor can use this case in business ethics, introductory management, human resource law or accounting courses targeting undergraduate or introductory MBA students. This case is best used in the beginning of the suggested courses, as the instructor introduces ethical dilemmas, ethical frameworks, and stakeholder theory. The case is designed so that students do not need a background in business or business ethics to be able to successfully complete the case analysis. Additionally, the case provides a platform to discuss the differences in an ethical vs an unethical manager and how to respond to such a situation. Theoretical bases: Many employees are afraid to report ethical wrongdoing to upper management, or to engage in ethical dissent. When upper management is receptive to reports of wrongdoing, ethical dissent within the organization to upper-level management has more organizational benefits than when the issue is shared with coworkers or external agencies. This is because upper management has the power to make a difference in the situation and may be able to keep the situation within the organization to eliminate possible reputation problems for the organization. The presented case can be utilized to discuss the importance of feeling safe in an organization as it pertains to reporting wrongdoing within the organization and how organizational culture and leadership can enhance or diminish that feeling.